Gut dysmotility in functional gastrointestinal disorders. Potential for therapeutic adjustment in terms of clinical case management - I. G. Pakhomova (Медицинский совет, 2020)
Gastrointestinal motility disorders can be a leading pathogenetic factor contributing to the development of many common gastroenterological diseases. Motor disorders can be a pathogenetic mechanism of development of both organic pathology (developmental abnormalities, acquired diseases, etc.), and functional gastrointestinal diseases associated with impaired nervous, humoral, metabolic and local regulation. (the latter are quite common in clinical practice). Correction of digestive motility disorders is determined by an understanding of the mechanisms of its complex regulation, which allows you to find the necessary points of application of drugs and select the necessary therapy. The motility of the gastrointestinal tract is primarily affected by prokinetics. Opioids used for many years are considered to be one of the most promising groups of prokinetics with proven effectiveness, they can both enhance and weaken the motor. A mu-, kappa-, and beta-receptor agonist, trimebutin, which acts on all receptors at the same time, coordinates the work of the intestines, and normalizes motility by reducing visceral sensitivity. Trimebutin favorably affects both hyperkinetic and hypokinetic forms of disorders of the motor activity of the gastrointestinal tract. This mechanism of action of trimebutin allows its effective use in patients with functional diseases of the digestive system, including those with the syndrome of their intersection. Trimebutin may be the drug of choice for such a combined pathology as irritable bowel syndrome and functional dyspepsia, the use of which is presented in the article on a clinical example of these two diseases.